2002
DOI: 10.1046/j.1532-5415.2002.50013.x
|View full text |Cite
|
Sign up to set email alerts
|

Side Rail Use and Bed‐Related Fall Outcomes Among Nursing Home Residents

Abstract: Despite high usage of bilateral side rails, they do not appear to significantly reduce the likelihood of falls, recurrent falls, or serious injuries. Bed-related falls remain clinically challenging. The data from this study, coupled with increasing reports of side rail-related injuries and deaths, compel us to seek and empirically test alternative interventions to prevent bed-related falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 50 publications
2
78
1
3
Order By: Relevance
“…Our findings are contrary to a nursing home study that found that bilateral side rail use did not decrease the risk of falls. 34 However, their comparison group was having no or 1 side rail raised, while ours was having no rails raised. It is also interesting to note that our study showed that having 1 to 2 bed rails raised is just as effective in reducing the risk of falling as having 3 to 4 rails raised.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are contrary to a nursing home study that found that bilateral side rail use did not decrease the risk of falls. 34 However, their comparison group was having no or 1 side rail raised, while ours was having no rails raised. It is also interesting to note that our study showed that having 1 to 2 bed rails raised is just as effective in reducing the risk of falling as having 3 to 4 rails raised.…”
Section: Discussionmentioning
confidence: 99%
“…Most disturbing was our finding of 15 incidents, representing 7 participants, who were observed with their arms or legs within the side rails. Considering the lack of evidence supporting the use of side rails (Capezuti et al, 2002(Capezuti et al, , 2007Oliver, 2002) in bed-related fall prevention and their potential fatal consequences (JCAHO, 2002), use of these devices should be limited to in-bed and transfer enablers but may require modification to reduce entrapment risk (Powell-Cope et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Most falls in nursing homes occur in the resident's room, especially during attempts to get in or out of bed (Agostini et al, 2001;Capezuti et al, 2002). Bed-exit alarms, designed to detect patient's movement out of bed, increase staff surveillance of cognitively and/or physically impaired residents at risk for bed-related falls.…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent secondary analysis of 319 nursing home residents with consistent bilateral bed rail use during the nighttime, those with dementia and behavioral symptoms were more likely to be restrained despite the finding that the bed rails did not significantly reduce the likelihood of falls, recurrent falls or serious injuries. 15 A gerontologic CNS intervention coupled with staff education was successful in reducing restraint use in hospitalized nursing home patients. 16 This randomized controlled trial engaged the gerontologic CNS in an admission assessment to assess fall risk within 12 to 36 hours, develop an individualized care plan to meet the patient's needs (especially to prevent restraint use), and to reassess and monitor high risk patients regularly.…”
Section: Research Findingsmentioning
confidence: 99%